Analysis on Consumer Demand Friction of local and Import Offal of Cattle in Traditional Market of Makassar City - I. M. Saleh; M. Ridwan; . Ja'far (Jurnal Ilmu dan Teknologi Peternakan, 2011)
This study aims to determine the friction in demand trends and the factors that cause a friction in consumer demand for local and import offal-good ex-Australia in the traditional markets of Makassar. Purposes of this research is for information and reference for our stakeholders on demand of local and import offal-good ex-Australia in the traditional markets of Makassar.The results of this study indicate that factors that cause a friction in demand for local and import offal-good ex-Australia are: product quality, affordability, accessibility and just try. Selection of local offal-good generally caused by factors of product quality (30.00%). While the types of import offal-good ex-Australia is commonly caused by the affordability of the price (39.00%). The trend friction in consumer demand switching from local offal-good type to import offal-good ex- Australia type can be seen from the degree of acquisition and loss. The results showed that the types of Local Offal-Good decreased from 47% to 42.33%. While the types of Import Offal-Good ex-Australia have increased from 53% to 57.33%. From these findings to forecast trends Import Offal-Good ex-Australia will dominate market share Offal-Good in the Traditional Market of Makassar.